Inside minds, beneath diseases: social cognition in amyotrophic lateral sclerosis-frontotemporal spectrum disorder. Issue 12 (22nd September 2020) - Lillo, Patricia; Caramelli, Paulo; Musa, Gada; Parrao, Teresa; Hughes, Ricardo; Aragon, Andres; Valenzuela, Daniel; Cea, Gabriel; Aranguiz, Rafael; Guimarães, Henrique Cerqueira; Rousseff, Laura; Gambogi, Leandro Boson; et al.
Abstract : Objective: To compare social cognition performance between patients with amyotrophic lateral sclerosis (ALS) and those patients with behavioural variant frontotemporal dementia (bvFTD). Methods: We included 21 participants with ALS, 20 with bvFTD and 21 healthy controls who underwent a comprehensive cognitive battery, including the short version of the Social Cognition and Emotional Assessment (Mini-SEA), which comprises the faux pas test and Facial Emotion Recognition Test (FERT); Mini-Mental State Examination; Frontal Assessment Battery; lexical fluency (F-A-S), category fluency (animals/minute), digit span (direct and backwards) tests and the Hayling test. A post hoc analysis was conducted with the patients with ALS divided into two subgroups: patients without cognitive impairment (ALScn; n=13) and patients with cognitive impairment (ALSci; n=8). Results: No significant difference was noted between participant groups in terms of the age, sex and education. ALS-total group and patients with bvFTD had similar disease durations. Patients with ALSci performed poorly when compared with controls with regard to the FERT (p<0.001), the faux pas (p<0.004) and the Mini-SEA (p<0.002) total scores. Moreover, patients with bvFTD performed poorly in comparison with controls in executive and social cognition tests. The performance of patients with ALSci was similar to that of patients with bvFTD, while the performance of patients with ALScn was similar to that of controls. Discussion: Our findings support a cognitive continuum between ALS and bvFTD and shed light on the cognitive heterogeneity of ALS, expanding its possible neuropsychological profiles.